2007
DOI: 10.1038/ng1976
|View full text |Cite
|
Sign up to set email alerts
|

A Mal functional variant is associated with protection against invasive pneumococcal disease, bacteremia, malaria and tuberculosis

Abstract: Toll-like receptors (TLRs) and members of their signalling pathway play an important role in the initiation of the innate immune response to a wide variety of pathogens1,2,3. The adaptor protein TIRAP mediates downstream signalling of 5,6. We report a case-control genetic association study of 6106 individuals from Gambia, Kenya, United Kingdom, and Vietnam, with invasive pneumococcal disease, bacteraemia, malaria and tuberculosis. Thirty-three SNPs were genotyped, including TIRAP S180L. Heterozygous carriage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
376
7
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(412 citation statements)
references
References 28 publications
23
376
7
3
Order By: Relevance
“…25 A recent study has found that TIRAP S180L polymorphism was associated with infectious diseases including TB in Africa and the heterozygous carriage of this variant was protective against TB. 26 Owing to the central role of TLR2 in the recognition of TB, we hypothesized that TLR2 polymorphisms were associated with susceptibility to disseminated disease, in particular TBM.…”
Section: Introductionmentioning
confidence: 99%
“…25 A recent study has found that TIRAP S180L polymorphism was associated with infectious diseases including TB in Africa and the heterozygous carriage of this variant was protective against TB. 26 Owing to the central role of TLR2 in the recognition of TB, we hypothesized that TLR2 polymorphisms were associated with susceptibility to disseminated disease, in particular TBM.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the inflammatory response, heterozygosity of the mannose binding lectin genotype predicts an advantage to fatal outcome of sepsis patients [28]. Furthermore, heterozygosity of the Toll-like receptor adaptor protein TIRAP/MAL has been associated with protection from tuberculosis, pneumococcal disease, and bacteremia [29]. Different molecular mechanisms for heterosis are discussed by Comings and MacMurray [30].…”
Section: Discussionmentioning
confidence: 99%
“…A polymorphism in the TIRAP gene which changes a serine to a leucine at amino acid 180 (S180L, C539T) has been shown to impair TLR2-mediated NF-κB signaling in in vitro experiments [27]. The 180L variant was less able to bind TLR2 in comparison to the 180S variant.…”
Section: Disease Mechanism 1: Macrophages Genetics and The Innate Imentioning
confidence: 99%